Assessment of implementation of antibiotic stewardship program in surgical prophylaxis at a secondary care hospital in Ras Al Khaimah, United Arab Emirates - Alshehhi, Hessa Saleh (Sci Rep, 2021)
Antibiotic overuse is a major factor for causing antibiotic resistance globally. However, only few studies reported the implementation and evaluation of antimicrobial stewardship programs in Gulf Cooperation Council. This study was conducted within 8-months periods to evaluate the effect of the newly implemented antibiotic stewardship program on improving the prescribing practice of surgical antibiotic prophylaxis in a secondary care hospital in the United Arab Emirates by releasing local hospital guidelines. The data of 493 in patients were documented in the predesigned patient profile form and the prescribing practice of surgical antibiotic prophylaxis for clean and clean-contaminant surgical procedures was compared and analyzed two months’ prior (period A) and post (period B) the implementation of antibiotic stewardship program. The 347 patient’s data (PD) were analyzed during period A and 146 PD during period B. The prescription of piperacillin/tazobactam was decreased from 2.4% from all surgical prophylaxis antibiotic orders in period A to 0% in period B. The appropriateness of the antibiotic therapy was found to differ non significantly for the selection of prophylactic antibiotic (p = 0.552) and for the timing of first dose administration (p = 0.061) between A and B periods. The total compliance was decreased non significantly (P = 0.08) from 45.3 to 40.2%. Overall, the guidelines have improved the prescribing practice of antibiotics prior to surgery. However, further improvement can be achieved by initiating educational intervention via cyclic auditing strategy.